Exercise In Nonambulatory People with Multiple Sclerosis - Edwards, Thomas (Université d'Ottawa / University of Ottawa, 2021)
Multiple sclerosis (MS) is an immune-mediated disorder characterized by neuroinflammation, demyelination, and neurodegeneration that results in the degradation of neurological structures within the central nervous system (CNS). This degradation of neurological structures often has a substantial impact on the ambulatory abilities of people living with MS, with an estimated 30% of the MS population requiring a wheelchair for mobility (i.e., nonambulatory). Unfortunately, current pharmacological interventions have limited efficacy for those with progressed disability and alternative strategies for disease management must be considered, such as exercise training. To date, most of the MS exercise training literature has not focused on nonambulatory people with MS, limiting evidence-based exercise recommendations for this population. As such, the central purpose of this dissertation was to inform exercise prescription and delivery for nonambulatory people with MS. In order to achieve this goal, three studies were conducted. The first study in this dissertation (presented across two manuscripts) evaluated the safety and physiological response of nonambulatory people with MS to three adapted exercise modalities (arm cycle ergometer, recumbent stepper, functional electrical stimulation cycle). This study determined that acute adapted exercise was well-tolerated by nonambulatory people with MS, with few adverse events reported across all exercise sessions. Notably, participants favoured recumbent stepper and functional electrical stimulation cycling exercise over arm cycle ergometer exercise. Further, participants were capable of exercising at an intensity that satisfied the American College of Sport Medicine’s criteria for moderate-to-vigorous physical activity on all adapted modalities. This suggests all tested modalities are capable of promoting improvements in health-related fitness outcomes. The second study, a systematic review and meta-analysis, explored outcome measures that capture ‘participation’ in MS exercise trials, and the influence of exercise training on ‘participation’. Described within the International Classification of Functioning, Disability and Health (ICF) as the “involvement in life situations”, ‘participation’ outcomes provide insight into the impact of MS on everyday life. Findings from this study demonstrated variability in how ‘participation’ has been captured, with an emphasis on items describing ‘mobility’. Further, the meta-analysis revealed that exercise training had a moderate, positive effect on outcomes that capture participation, a novel finding regarding the benefits of exercise training in MS. The final study of this dissertation, an online-based survey, identified perceived exercise benefits, barriers, and needs among nonambulatory people with MS. This study demonstrated that nonambulatory people with MS perceive health improvements and personal accomplishments as the greatest benefits associated with exercise engagement. The sample also cited environmental challenges and MS symptoms as prominent barriers to exercise engagement. The current sample identified that exercise facilities, specifically exercise equipment, were failing to accommodate their exercise needs. Collectively, the findings from this dissertation will help address prominent gaps in the exercise training literature involving nonambulatory people with MS. Addressing such gaps will contribute to advancing evidence-informed exercise interventions, promoting measurable health improvements, and ultimately increasing engagement in exercise for nonambulatory people with MS,
Keywords: Multiple Sclerosis; Exercise; Nonambulatory